Capture of primordial black holes in extrasolar systems. Issue 8 (1st August 2022) - Lehmann, Benjamin V.; Webber, Ava; Ross, Olivia G.; Profumo, Stefano
Abstract: The vast datasets associated with extrasolar systems promise to offer sensitive probes of new physics in the near future. We consider the possibility that such systems may capture primordial black holes (PBHs) or other exotic compact objects, giving rise to unique observational signatures. We estimate the rate of captures by extrasolar systems, accounting for several distinct mechanisms. We find that the capture rate is negligible unless PBHs account for the entirety of dark matter in a narrow mass range just above the threshold of existing constraints from evaporation. In this scenario, luminous evaporating PBHs may be detectable by exoplanet searches.